2020
DOI: 10.1002/pbc.28787
|View full text |Cite
|
Sign up to set email alerts
|

A POETIC Phase II study of continuous oral everolimus in recurrent, radiographically progressive pediatric low‐grade glioma

Abstract: Background: To evaluate efficacy, pharmacokinetics (PK) and pharmacodynamics of single-agent everolimus in pediatric patients with radiographically progressive lowgrade glioma (LGG). Methods: Everolimus was administered at 5 mg/m 2 once daily as a tablet or liquid for a planned 48-week duration or until unacceptable toxicity or disease progression. Patients with neurofibromatosis type 1 were excluded. PK and pharmacodynamic endpoints were assessed in consenting patients. Results: Twenty-three eligible patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…Low-grade gliomas have activation of mTOR as well as MAPK ( 57 ). Treatment of low-grade gliomas with the mTOR inhibitor everolimus stabilizes disease in many patients and produces regressions in some patients ( 58 , 59 ). Clinical trials are currently underway in pediatric low-grade glioma combining MEK and mTORC1-inhibiting rapalogs (NCT04485559).…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade gliomas have activation of mTOR as well as MAPK ( 57 ). Treatment of low-grade gliomas with the mTOR inhibitor everolimus stabilizes disease in many patients and produces regressions in some patients ( 58 , 59 ). Clinical trials are currently underway in pediatric low-grade glioma combining MEK and mTORC1-inhibiting rapalogs (NCT04485559).…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical trials, mucositis, stomatitis, or aphthous ulcers were the only reported cAE. 44,46,47,[51][52][53][54] Curatolo et al 44 reported similar rates of stomatitis/mouth ulceration in younger patients (<6 years of age) and older patients (6-18 years of age).…”
Section: Mammalian Target Of Rapamycin (Mtor) Inhibitorsmentioning
confidence: 93%
“…Another oral MEK inhibitors, binimetinib (MEK-162) and cobemitinib have completed or progressed phase 1 trials in children with recurrent, refractory or progressive pLGG and other BRAF-mutated recurrent pediatric solid tumors which are Ras/Raf pathway activated malignancies [ 50 ]. Therapies targeting the mTOR pathway, such as everolimus, are also currently being tested evaluating everolimus in children with recurrent/progressive pLGG [ 51 52 ]. The phase 2 study of everolimus showed the results of 2 PR, 10 SD without CR in 23 children with recurrent and/or progressive pLGGs.…”
Section: Targeted Treatments For Plggmentioning
confidence: 99%